THE EFFECT OF ORGANIZATIONAL CULTURE, EMPLOYEE ENGAGEMENT, AND ORGANIZATIONAL COMMUNICATION ON ISLAMIC PERFORMANCE WITH KNOWLEDGE SHARING AS INTEVENING VARIABLES ΈCASE STUDY ON BANK BRI SYARIAH KC SEMARANGΉ - Mukhamad Miftahkhus Salam; Bobur Sobirov (Imara: JURNAL RISET EKONOMI ISLAM, 2021)
The Effect of Organizational Culture, Employee Engagement, And Organizational Communication On Islamic Performance With Knowledge Sharing As Intervening Variables (Case Study On Bank BRI Syariah KC Semarang). Essay. Faculty of Economics and Islamic Business, S1 Islamic Banking Study Program, IAIN Salatiga. Supervisior Endah Nur Fitryanti, M. M. The purpose of this study how to effect of Organizational Culture (X1) Employee Engangement (X2) and Oraganizational Communication (X3) on Islamic Performance (Y) with Knowledge Sharing (Z) as an Intervening Bariable in Bank BRI Syariah KC Semarang. In this study, using quantitative methods by processed primary data obtained through a questionnaire given to BRI Syariah KC Semarang employees as many 37 respondents using saturated sampling techniques. Then the data obtained were processed with SPSS Version 20. The analysis used in this study included instrumen tests, statistical tests, classical test, and path analysis. Based on the test result show the results: (1) Organizational culture has not effect on knowledge sharing. (2) Employee engangement has a positive and not significant effect on knowledge sharing. (3) Organizational communication has a positive and significant effect on knowledge sharing. (4) Organizational culture has not effect on islamic performance. (5) Employee engagement has not effect on islamic performance. (6) Organizational communication has not effect on islamic performance. (7) Knowledge sharing has a positive and not significant on islamic performance. (8) Knowledge sharing has not mediation the effect of organizational culture on islamic performance. (9) Knowledge sharing has not mediation the effect of employee engagement on islamic performance. (10) Knowledge sharing mediate the organizational communication on islamic performance